1991
DOI: 10.1021/bi00246a009
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for domain organization within the 61-kDa calmodulin-dependent cyclic nucleotide phosphodiesterase from bovine brain

Abstract: The complete amino acid sequence of the 61-kDa calmodulin-dependent, cyclic nucleotide phosphodiesterase (CaM-PDE) from bovine brain has been determined. The native protein is a homodimer of N alpha-acetylated, 529-residue polypeptide chains, each of which has a calculated molecular weight of 60,755. The structural organization of this CaM-PDE has been investigated with use of limited proteolysis and synthetic peptide analogues. A site capable of interacting with CaM has been identified, and the position of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
70
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 39 publications
6
70
0
Order By: Relevance
“…2A, which shows that the heat effects during initial injections are comparable and are followed by a quick disappearance of heat effects in later injections, indicating that saturation of Ca (Table I). This includes the PDE peptide, which in a previous study had been observed to bind Ca 2ϩ -CaM with a stoichiometry of 2 peptides per CaM molecule (53). The results here, as well as those of another study (22), however, strongly suggest a 1:1 mode of binding for this PDE peptide to CaM.…”
Section: Resultssupporting
confidence: 61%
“…2A, which shows that the heat effects during initial injections are comparable and are followed by a quick disappearance of heat effects in later injections, indicating that saturation of Ca (Table I). This includes the PDE peptide, which in a previous study had been observed to bind Ca 2ϩ -CaM with a stoichiometry of 2 peptides per CaM molecule (53). The results here, as well as those of another study (22), however, strongly suggest a 1:1 mode of binding for this PDE peptide to CaM.…”
Section: Resultssupporting
confidence: 61%
“…PDE families have different responses to inhibitors. PDE1s are stimulated by Ca 2+ / CaM activity (134,135), and PDE4 regulates cAMP signaling by its PKA-mediated phosphorylation (136 -138). PKA is a major target of cAMP-regulated exocytosis in exocrine cells.…”
Section: +mentioning
confidence: 99%
“…Mammalian PDEs form a superfamily of enzymes comprised of 10 families of PDEs which differ in amino acid sequences (2, 3, 9 -11), substrate specificities, inhibitor sensitivities, modes of regulation, and tissue distribution. PDEs are chimeric proteins (12)(13)(14)(15) which contain specific domains that provide for cyclic nucleotide hydrolysis, interaction with allosteric/regulatory molecules, autoinhibition, subcellular localization, and perhaps for other functions as well (12,16,17). For mammalian PDEs, the regulatory domains appear to reside mainly in the amino-terminal portions of the proteins.…”
mentioning
confidence: 99%